The Effects of Google Classroom in Learning Syntactic Structure - Siahaan, Mungkap Mangapul (CV. Ridwan Publisher, 2021)
The purpose of this research is to respond to the bold learning at HKBP Nommensen University Pematang Siantar in the middle of compiling a strategic plan for implementing online education. At the same time, the misconceptions and myths of the difficulties of online teaching and learning, the technology available to support online support, the support and compensation required for high-quality instructors, and the needs of online students create challenges for such vision statements and planning documents. The method of this study is quantitative research and adapted Shaharance et.al (2016) questionnaire as the instrument to collect the data They are divided into four classes, two classes learn using Google Class and the other 2 learn without learning online. The research method used in this research is quantitative research and a questionnaire is used as data. The results showed that student achievement was higher after they studied Syntax Structure using Google Class.